The anarchy : the relentless rise of the East India Company - Dalrymple, William (Bloomsbury Publishing, 2019)
In August 1765, the East India Company defeated the young Mughal emperor and set up, in his place, a government run by English traders who collected taxes through means of a private army. The creation of this new government marked the moment that the East India Company ceased to be a conventional company and became something much more unusual: an international corporation transformed into an aggressive colonial power. Over the course of the next 47 years, the company's reach grew until almost all of India south of Delhi was effectively ruled from a boardroom in the city of London. The Anarchy tells one of history's most remarkable stories: how the Mughal Empire-which dominated world trade and manufacturing and possessed almost unlimited resources-fell apart and was replaced by a multinational corporation based thousands of miles overseas, and answerable to shareholders, most of whom had never even seen India and no idea about the country whose wealth was providing their dividends. Using previously untapped sources, Dalrymple tells the story of the East India Company as it has never been told before and provides a portrait of the devastating results from the abuse of corporate power.